2020
DOI: 10.1101/2020.06.02.20119313
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early phase of the COVID-19 outbreak in Hungary and post-lockdown scenarios

Abstract: COVID-19 epidemic has been suppressed in Hungary due to timely non-pharmaceutical interventions, prompting a huge reduction in the number of contacts and transmission of the virus. This strategy was effective in preventing epidemic growth and reducing the incidence of COVID-19 to low levels. In this report, we present the first epidemiological and statistical analysis of the early phase of the COVID-19 outbreak in Hungary. Then, we establish an age-structured compartmental model to explore alternative post-loc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 46 publications
1
37
0
1
Order By: Relevance
“…Data from different sources including online surveys, depersonalized aggregated mobile cell and traffic data showed a drastic, 60-90% reduction in the number of contacts and extreme reduction in mobility. (Röst et al 2020) It has been shown with the use of mobility and COVID-19 epidemiology data from the European countries that successful restrictive policy can significantly contribute to the suppression of the SARS-CoV-2 pandemic. (Vokó and Pitter 2020) Furthermore, consistently with the low level of seropositivity reported in our study, the rate of incident cases registered by the National Public Health Center in Hungary throughout the timeframe of the testing was low as well.…”
Section: Discussionmentioning
confidence: 99%
“…Data from different sources including online surveys, depersonalized aggregated mobile cell and traffic data showed a drastic, 60-90% reduction in the number of contacts and extreme reduction in mobility. (Röst et al 2020) It has been shown with the use of mobility and COVID-19 epidemiology data from the European countries that successful restrictive policy can significantly contribute to the suppression of the SARS-CoV-2 pandemic. (Vokó and Pitter 2020) Furthermore, consistently with the low level of seropositivity reported in our study, the rate of incident cases registered by the National Public Health Center in Hungary throughout the timeframe of the testing was low as well.…”
Section: Discussionmentioning
confidence: 99%
“…A subsets of papers use a metapopulation approach accounting also for the age-stratification and contact matrices within each subpopulation. In this group we find papers that evaluate the risks of importation of cases from China in the early phases of the pandemic [22] , model the first wave [119] , [121] , [122] , [123] , [147] and investigate reopening scenarios [106] , [120] .…”
Section: Epidemic Modelsmentioning
confidence: 99%
“…1 . Several studies [ 3 , 14 , 39 , 40 , 45 , 55 ] have proposed somewhat similar models for of COVID-19.…”
Section: Transmission Dynamics Modelmentioning
confidence: 99%
“…Many studies have investigated for different countries; here, we use estimated from the Hungarian data [ 45 ]. From relation ( 9 ), given that all other parameters are determined, we can calculate .…”
Section: Transmission Dynamics Modelmentioning
confidence: 99%